Trade liberalization in a joint spatial inter-temporal trade model - Hui Huang; John Whalley; Shunming Zhang (Center for Economic Studies and ifo Institute (CESifo), 2005)
This paper considers liberalization of trade in both inter-temporal intermediation services and goods in a joint spatial-inter-temporal trade model. Joint multi-commodity spatial intertemporal models are not (to our knowledge) used in the trade literature as general comparative statics results are unavailable and (in the presence of incomplete markets) existence can also be an issue. Here we use numerical simulation methods. We first consider world with service trade autarky in which there is no domestic intermediation service provision, and service trade liberalization involves costless inter-temporal intermediation provided by foreign service providers. This simple treatment allows us to model service trade liberalization as removing period by period budget constraints for domestic consumers. In such a world, if nonzero tariffs apply to spatial trade we present an example showing how service trade liberalization can be welfare worsening. One implication is that negotiations on services in the WTO General Agreement on Trade in Services (GATS) need not be welfare improving if there are also ongoing tariff negotiations. We then expand the model to capture a more complex world where costly intermediation services can be provided by both withincountry and foreign providers. We again illustrate how services liberalization can be welfare worsening. We finally discuss whether welfare worsening service trade liberalization is likely in a real-world situation of highly restricted services trade and considerably more open goods trade, and when services trade are around 1/3 of total goods and services trade as is often claimed from available global service trade data.
Keywords: F11; F00; 330; Internationaler Dienstleistungsverkehr; Aussenhandelsliberalisierung; GATS; Aussenwirtschaftstheorie; Zwei-Länder-Modell; Zeitökonomik; Allgemeines Gleichgewicht; Wohlfahrtseffekt; Theorie